CD73 Expressed on γδ T Cells Shapes Their Regulatory Effect in Experimental Autoimmune Uveitis - Liang, Dongchun (Public Library of Science, 2016)
γδ T cells can either enhance or inhibit an adaptive immune response, but the mechanisms involved are not fully understood. Given that CD73 is the main enzyme responsible for conversion of AMP into the immunosuppressive molecule adenosine, we investigated its role in the regulatory function of γδ T cells in experimental autoimmune uveitis (EAU). We found that γδ T cells expressed different amounts of CD73 during the different stages of EAU and that low CD73 expression on γδ T cells correlated with enhanced Th17 response-promoting activity. Functional comparison of CD73-deficient and wild-type B6 (CD73+/+) mice showed that failure to express CD73 decreased both the enhancing and suppressive effects of γδ T cells on EAU. We also demonstrated that γδ T cells expressed different amounts of CD73 when activated by different pathways, which enabled them to either enhance or inhibit an adaptive immune response. Our results demonstrate that targeting CD73 expression on γδ T cells may allow us to manipulate their pro- or anti-inflammatory effect on Th17 responses.